Relationship between organizational culture and organizational innovativeness at the private universities in Iran - Ashraf, Giti; Abd. Kadir, Suhaida; Lope Pihie, Zaidatol Akmaliah; Mat Rashid, Abdullah (IDOSI Publications, 2013)
The aim of this study was to examine the association between organizational culture and organizational innovativeness in private universities in Iran using survey method. A sample of 485 full time faculty members was selected based on simple one stage cluster sampling. The findings indicated that significant positive relationships were found between three types of organizational culture and organizational innovativeness. They were; the adhocracy, the market and the clan cultures respectively. However, the hierarchy culture showed a non-significant correlation with organizational innovativeness. In addition, the adhocracy culture contributed most to predicting organizational innovativeness. This study once more demonstrated that each organization has its own organizational culture. It is proposed to identify and develop the appropriate organizational culture which makes it possible for the administrators, academic members and students to engage in innovative activities